(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
We report a case of recurrent mucinous carcinoma of the breast in a 60 year old female who presented with two separate lumps on the left chest wall for 1 year. She gave the history of left sided mastectomy 15 years ago and hysterectomy 10 years ago. The patient did not seek any medical attention for the lumps since she noticed them a year ago. On examination, there were two lumps larger one measuring 7.5 x 5 cm and other smaller one measuring 3 x 2.5 cm. Core needle biopsy showed ductal carcinoma. CT scan was done which showed post-operative status of left side breast cancer with left chest wall mass and metastatic left axillary mass. Ultrasonography of whole abdomen and bony scan was done and no metastasis was seen. She underwent en-bloc excision of the tumor with involved muscle. Histopathology was done from two different centers both revealed Mucinous carcinoma of the breast. She was advised to take adjuvant chemotherapy.